A pilot study to examine the effects of beta-alanine and sodium citrate (CarnoRushTM, Olimp®) supplementation on climbingspecific performance - Krzysztof SAS-NOWOSIELSKI; Piotr KACZKA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. Competitive and rock climbers primarily rely on anaerobic energy metabolism, and acidosis may limit their performance. It is supposed that supplements that improve buffering capacities of the body, like β-alanine (BA) and sodium bicarbonate/citrate (SB/SC), may be useful in this sport. The aim of the study was to explore the efficacy of co-supplementation of BA and SC on climbing performance. Material and methods. 13 climbers (age 40.2 ±7.9 years, height 175.4 ±8.4 cm, body mass 68.6 ±13.9 kg, UIAA metric 9.2 ±0.8) were randomly assigned to the supplement (SG; n = 7) or control group (CG: n = 6). For 4 wks, the SG was taking a supplement containing: BA 4 g·d, SC 0.6 g·d and histidine 0.2 g·d. Climbers were tested on two bouldering circuits done back and forth until exhaustion: "hard" and "easy". Results. Climbers from the SG significantly increased their performance in terms of the number of moves done in both circuits, hard F(1,11) = 5.44, p = 0.04, ɳ2 = 0.33 and easy F(1,11) = 4.91, p = 0.05, ɳ2 = 0.33. Within group effect sizes were d = 0.49 and 0.46 for SG and 0.18 and 0.27 for CG, respectively. Conclusions. Co supplementation of BA and SC may improve performance in climbing, especially efforts lasting at least about one minute of continuous effort.